"A Black Rather Well-Known South African Recently Arrived in London": Critical Responses to Todd Matshikiza's Chocolates for My Wife. Issue 1 (2nd January 2020) - Thorpe, Andrea Susan
ABSTRACT: This article studies the intersections between Todd Matshikiza's celebrity in South Africa and in Britain and the critical reception of his autobiography, Chocolates for My Wife (1961). Matshikiza's renown as the composer of the South African jazz musical King Kong, staged in Britain in the early 1960s, contributed to the development of his only full-length literary work, while the ambivalent and frequently racist media discourse around King Kong reverberated into readings of his autobiography. By exploring how Matshikiza's writing was perceived and presented by his publishers, alongside an analysis of the responses by British and South African literary critics, this article shows how Matshikiza and his writing served as a site for debates about the role of literature in relation to apartheid. Matshikiza's exile and banning necessitated a new, British audience for his work, and also resulted in a deferred re-issuing and re-reading of his writing in the early 1980s, when Chocolates for My Wife was unbanned. This study contributes to the growing body of knowledge about the complex roles of exiled South African cultural figures and intellectuals in relation to international resistance to apartheid from the early 1960s onwards.